HRM in public private partnerships: working in a health production system - Bishop, Simon (2011)
This study explores the changing nature of employment and employment management within multi-organisational public services ‘partnerships’. In line with international trends, a major feature of the 1997-2010 New Labour government’s public policy was encouraging partnerships between organisations of all sectors to run public services. Within healthcare, central government has increasingly been seen as taking on a role of market regulator, with organisations from all sectors allowed to plan as well as provide public services (Illife and Munro, 2000). As part of this picture, bringing private companies into partnership arrangements with the National Health Service has been seen as a catalyst for workforce re-configuration and employment change through furthering the reach of private sector type Human Resource Management. However, research has illustrated how inter-organisational contracts can also restrict an organisations choice of employment practice, disrupt the direct relationship between managers and employees, and undermine any aspirations for fair or consistent employment (Marchington et al, 2005). In more recent healthcare partnerships, employment is further complicated as partnerships involve powerful professional groups with their own protected employment systems and established norms of practice. This study seeks to investigate the prospects for HRM within such a professionalised partnership context through comparative case study of two Independent Sector Treatment Centres (ISTCs) operating under differing employment regulations and contractual agreements. In both cases, private sector management sought to impose a more ‘rationalised’ and standardised approach to work with a greater focus on outputs and productivity, placing ISTCs at the forefront of the Fordist ‘scientific-bureaucratic’ (Harrison, 2002) approach to medicine. However, the study identifies a number of limits to the degree to which the management of the private health care companies could shape HRM practices in line with these aims. The thesis also examines how being separate from, or integrated with, existing National Health Service organisations can lead to different types of contingencies affecting work and employment, and multiple varieties of inconsistency across the workforce. The findings of the study are explored in terms of the implications for public policy, health service management and HRM theory.